From weapons to books: an analysis of the denialist discourse in the book A verdade sufocada by Carlos Alberto Brilhante Ustra: From weapons to books: an analysis of the denialist discourse in the book A verdade sufocada by Carlos Alberto Brilhante Ustra (Revista de História da UEG (REVHIST), 2021)
This article aims to analyze the textual and stylistic dimensions present in Carlos Alberto Brilhante Ustra's denialist narrative in A verdade sufocada: a História que a esquerda não quer que o Brasil conheça and, for that, the tropological mechanisms proposed by Hayden White will guide this investigation. Demonstrated the explanatory strategies used by the colonel to convince his audience about his worldview, as well as the apprehension he makes of the past in the current context of war of memories, it is expected to contribute to the construction of an ethical and humanly responsible response about the traumatic past of the Civil-Military Dictatorship of 1964-1985.Keywords: Denialism. Dictatorship of 1964-1985. War of memories.